Antibacterial activity of some essential oils (Damascus University Journal of agriculture sciences, 2021)
To evaluate the antibacterial activity of four plant essential oils (Rosmarinus officinalis, Salvia fruticosa, Thymus syriacus, Thymus serpyllum), against five bacterial strains. The selected essential oils were extracted by steam distillation method, and the main active constituents of the essential oils and their concentrations were determined by using  Gas Chromatography and GC Mass spectrometry. the essential oils were screened against four Gram-negative bacterial strains and one Gram-positive bacterial strains at four different concentrations using disc diffusion method. Majority of the oils showed different antibacterial activity against the tested strains according to their concentration.
Keywords: Essential oil; Oil components; Antibacterial activity